Sosok Pendidik dalam Tinjauan Al-Qur'an dan Hadist (Studi Literatur) - Hefrita, Nelly Octovia; Hasni, Walidatil; Satriadi, Inong (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study aims to find out the figure of educators in the review of the Qur'an and Hadith through literature analysis. The method used in this study is a literature review using a qualitative approach and descriptive analysis. Descriptive analysis is used to present characteristics, patterns, and trends that emerge from data obtained from articles published on Google Scholar. The results of data analysis show that educators and educational institutions are systems that must be developed in accordance with Sharia. Both have interdependent roles with each other. Educators cannot carry out all duties and responsibilities, no learners as human resources receive education. Conversely, educational institutions are also a place to run the system and learning process for students.